Recurrent Laryngeal Nerve Palsy After Thyroid Surgery and Literature Review - Dutta, H; Sinha, BK; Baskota, DK (Nepalese Journal of ENT Head and Neck Surgery, 2012)
Nepalese Journal of ENT Head and Neck Surgery Vol.2 No.2 Issue 2 (July-Dec 2011) 27-28 DOI: http://dx.doi.org/10.3126/njenthns.v2i2.6803